Managing and Predicting the Condition of Paved Road Network in Finland: Essential Technical Information - Anne Hämäläinen; Kalle Vaismaa; Pauli Kolisoja (The Baltic Journal of Road and Bridge Engineering, 2025)
The condition of roads is recognised as a critical foundation for economic prosperity and, therefore, requires continuous maintenance. Effective management of roads necessitates a clear understanding of the road network’s condition. This study aims to identify the technical condition information currently utilised, needed, and missing within the context of paved roads in Finland. The study is qualitative, with data consisting of fifteen semi-structured interviews: road authorities (7), maintenance specialists in road condition analysis (6), and contractors (2). Based on the results, recommendations were given for monitoring the road network. For monitoring functional conditions, a new method for detecting defects must be introduced, with other measurable parameters being better managed. For monitoring structural conditions, it is recommended to start regular deflection measurements and define the condition criteria. Additionally, more up-to-date information is needed on the condition of drainage structures. With the help of these findings and recommendations, it is possible to enhance the monitoring, management, and optimization of the road network’s condition in a more data-driven manner.